Pengaruh Pemasaran Digital, Citra Produk, dan Perilaku Konsumen terhadap Keputusan Pembelian Mie Gacoan di Yogyakarta pada Masa Pandemi Covid-19 - Puspitasari Putri Handayani; Tri Harsini Wahyuningsih (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2022)
This study aims to analyze the effect of digital marketing, product image, and consumer behavior on purchasing decisions for Mie Gacoan in Yogyakarta during the Covid-19 pandemic. Samples were taken using a non-probability sampling technique using a purposive sampling method, who had bought gacoan noodles in Yogyakarta during the Covid-19 pandemic. 165 respondents in this study filled out a questionnaire via a google form. After the data has been collected, instrument tests, basic assumption tests, and classical assumption tests are carried out. All data pass the test, the proceed with hypothesis testing. The results of the t-test and multiple linear regression show that digital marketing has a positive and significant effect on purchasing decisions, product image variables, and consumer behavior. Based on the coefficient of determination test (Adjusted ) it was found that 46.6% of purchasing decisions for gacoan noodles in Yogyakarta can be explained by digital marketing, product image, and consumer behavior, while the remaining 53.4% is explained by other variables which were not included in this study.